2014
DOI: 10.3389/fnbeh.2014.00263
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pain: modeling decision-making deficits in chronic pain

Abstract: Risky decision-making seems to be markedly disrupted in patients with chronic pain, probably due to the high cost that impose pain and negative mood on executive control functions. Patients’ behavioral performance on decision-making tasks such as the Iowa Gambling Task (IGT) is characterized by selecting cards more frequently from disadvantageous than from advantageous decks, and by switching often between competing responses in comparison with healthy controls (HCs). In the present study, we developed a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…[37,38] A preliminary study (N=30) suggests that patients with fibromyalgia showed high sensitivity to immediate gains at the expense of future losses, as compared with controls, on the Iowa Gambling task, a task of decision making in the context of varying reward and punishment contingencies. [39] Chronic pain patients demonstrated impaired probabilistic learning, perseverating responses that yield high immediate gains but higher future losses, although these patients also exhibited more random, less perseverative behavior than healthy controls. [39] Results of these studies of risk-based decision-making suggest that additional research is necessary to further explore the role of chronic pain in executive functioning in fibromyalgia patients and to determine whether reward-based decision-making is altered in other chronic pain conditions.…”
Section: Literature Summary Neurocognitive Impairmentmentioning
confidence: 95%
See 2 more Smart Citations
“…[37,38] A preliminary study (N=30) suggests that patients with fibromyalgia showed high sensitivity to immediate gains at the expense of future losses, as compared with controls, on the Iowa Gambling task, a task of decision making in the context of varying reward and punishment contingencies. [39] Chronic pain patients demonstrated impaired probabilistic learning, perseverating responses that yield high immediate gains but higher future losses, although these patients also exhibited more random, less perseverative behavior than healthy controls. [39] Results of these studies of risk-based decision-making suggest that additional research is necessary to further explore the role of chronic pain in executive functioning in fibromyalgia patients and to determine whether reward-based decision-making is altered in other chronic pain conditions.…”
Section: Literature Summary Neurocognitive Impairmentmentioning
confidence: 95%
“…[39] Chronic pain patients demonstrated impaired probabilistic learning, perseverating responses that yield high immediate gains but higher future losses, although these patients also exhibited more random, less perseverative behavior than healthy controls. [39] Results of these studies of risk-based decision-making suggest that additional research is necessary to further explore the role of chronic pain in executive functioning in fibromyalgia patients and to determine whether reward-based decision-making is altered in other chronic pain conditions. In contrast, other studies examining executive functioning in fibromyalgia revealed mixed findings, with some demonstrating deficits compared with those without fibromyalgia [14,38,40] and others not [12,41] , highlighting the possible influence of mediating and moderating factors, discussed in detail below.…”
Section: Literature Summary Neurocognitive Impairmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Individuals with chronic pain may have compromised decision-making capabilities [34][35][36][37][38][39][40] as "chronic pain should be considered a 'cognitive state,' and that it may thus be competing with other cognitive abilities." 34 Furthermore, daily coping of the multiple aspects of pain management can become an overpowering experience for individuals suffering from chronic pain.…”
Section: Vulnerable State Of Sufferers Of Chronic Painmentioning
confidence: 99%
“…Individuals with chronic pain may have compromised decision-making capabilities 3440 as “chronic pain should be considered a ‘cognitive state,’ and that it may thus be competing with other cognitive abilities.” 34 Furthermore, daily coping of the multiple aspects of pain management can become an overpowering experience for individuals suffering from chronic pain. 23 Individuals with such compromised decision-making capabilities, according to Waisel’s definition, 41 can be labeled a vulnerable population.…”
Section: Wearable Healthcarementioning
confidence: 99%